OPTIMALISASI PERAN SERTA KARANG TARUNA DIDALAM MENGEMBANGKAN POTENSI WISATA DI ALIRAN SUNGAI TELAGA WAJA KABUPATEN KARANGASEM - Putu Agus Prayogi; Komang Krishna Yogaantara; Made Hedy Wartana (Synergy and Society Service, 2023)
The socialization and training activities carried out in the implementation of Community Service at the Faculty of Business and Tourism, Triatma Mulya University in Tangkup village, Sidemen District, Karangasem are a continuation of the KKN program in the previous period. This activity involves lecturers who have competence in the field of training provided. During the activity, all participants were present for the 2 days of the activity. The participants, in this case members of the Tangkup village youth organization, were very enthusiastic in participating in the training activities. This is certainly very encouraging considering that the participants will be prepared to manage tourism potential in their own villages. It is hoped that in the future, through this training, Karang Taruna members will be able to optimally develop their tourism potential so that Tangkup Village can develop as one of the tourist villages in Bali.